Internal audit quality : developing a quality assurance and improvement program - Pitt, Sally-Anne. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2014)
"Deliver increased value by embedding quality into internal audit activitiesInternal Audit Quality: Developing a Quality Assurance and Improvement Program is a comprehensive and authoritative guide to better practice internal auditing. Written by a global expert in audit quality, this guide is the first to provide complete coverage of the elements that comprise an effective internal audit quality assurance and improvement program. Readers will find practical solutions for monitoring and measuring internal audit performance drawn from The IIA's International Standards for the Professional Practice of Internal Auditing, and complemented by advice and case studies from leading audit practitioners from five different continents. Major corporate and financial collapses over the past decade have challenged the value of internal audit. With an increased focus on internal audit's role in good governance, management is increasingly demanding that internal audit provides assurance of the quality of its own activities. The IIA standards provide a framework for audit quality in the form of mandatory guidance. Recent research indicates that the majority of internal audit functions do not fully comply with the standards and, as a result, are not servicing the needs of their organizations as well as they might. Internal Audit Quality offers a roadmap to internal audit quality, providing readers the guidance they need to: Embed quality into all elements of internal audit from strategic and operational planning down to day-to-day tasks Create well-defined internal audit programs and procedures Independently self-assess internal audit quality and performance Conform with the IIA standards and better practice Provide assurance over internal audit efficiency and effectiveness Deliver value by meeting stakeholder expectations As a key component of good governance, internal audit is on the rise. The days of retrospective, compliance-focused auditing is a thing of the past. Organizations expect more of internal audit, and many internal audit activities are accepting the challenge. Rather than relying on audit supervision and external assessments, modern auditors are embedding quality into audit activities to create effective programs. For the auditor looking to distinguish themselves as leading edge, Internal Audit Quality provides the guidance that enables the right work, at the right time, in the right way"--
"This book provides complete coverage of the elements that comprise an effective internal audit quality assurance and improvement program. The book offers solutions for monitoring and measuring internal audit performance drawn from the IIA's International Standards for the Professional Practice of Internal Auditing, and complemented by advice and case studies from leading audit practitioners from five different continents"--
Includes index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Auditing, Internal; Quality control; BUSINESS & ECONOMICS -- Auditing; Auditing, Internal; Quality control; Electronic books; Electronic books